2020
DOI: 10.1039/d0cc90367a
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Cu2O template synthesis of high-performance PtCu alloy yolk–shell cube catalysts for direct methanol fuel cells

Abstract: Correction for ‘Cu2O template synthesis of high-performance PtCu alloy yolk–shell cube catalysts for direct methanol fuel cells’ by Sheng-Hua Ye et al., Chem. Commun., 2014, 50, 12337–12340, DOI: 10.1039/C4CC04108A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…16,20,25,26 Therefore, the focus of this study is Cu 2 O. As an important semiconductor, cuprous oxide (Cu 2 O) has been widely used in several important catalytic reactions, such as CO oxidation, 27−29 methanol synthesis, 30,31 water−gas conversion reactions, 32,33 and NO x conversion. 16,20,27 Recent experimental studies show that different surface facets of Cu 2 O nanocrystals have different activities for NO reduction by CO. 20,27 Gao et al 20 facets and cubes with exposed (100) facets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,20,25,26 Therefore, the focus of this study is Cu 2 O. As an important semiconductor, cuprous oxide (Cu 2 O) has been widely used in several important catalytic reactions, such as CO oxidation, 27−29 methanol synthesis, 30,31 water−gas conversion reactions, 32,33 and NO x conversion. 16,20,27 Recent experimental studies show that different surface facets of Cu 2 O nanocrystals have different activities for NO reduction by CO. 20,27 Gao et al 20 facets and cubes with exposed (100) facets.…”
Section: Introductionmentioning
confidence: 99%
“…As for CuO, it is speculated that Cu 2 O is formed by the reduction of CuO by CO and acts as a catalyst for the NO + CO reaction. ,,, Therefore, the focus of this study is Cu 2 O. As an important semiconductor, cuprous oxide (Cu 2 O) has been widely used in several important catalytic reactions, such as CO oxidation, methanol synthesis, , water–gas conversion reactions, , and NO x conversion. ,, Recent experimental studies show that different surface facets of Cu 2 O nanocrystals have different activities for NO reduction by CO. , Gao et al found that among the three main exposed low-index crystal planes (110), (111), and (100) of Cu 2 O, rhombic dodecahedral nanocrystals with exposed (110) facets possess better catalytic performance for NO reduction by CO than octahedrons with exposed (111) facets and cubes with exposed (100) facets. It is observed that the main product is N 2 O at low temperature, while with the increases of temperature, N 2 , which is mainly produced by N 2 O decomposition, becomes the major product.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 Second, the regulated electronic structure of Pt by Cu alloying also can promote the MOR process. 53,57 For Pt catalysts, the indirect MOR route occurring on Pt NPs usually means that methanol is oxidized first to CO or other carbonaceous intermediates and consequently causes the poisoning of the Pt/C catalysts. 58 For the case here, the alloying with Cu downshifts the d-band center of Pt, as indicated by the XPS data shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is recognized that the d -band center will be upshifted by alloying Pt with other metals, suggesting that the electrocatalytic activity can be effectively improved through introduction of other components. To date, Pd, Zn, Co, Ag, Mn, Au, Sn, Ru, Cu, and so forth have been incorporated into the Pt matrix. Furthermore, the introduction of oxophilic metals can also facilitate the removal or oxidation of poisoning CO intermediates formed on the Pt surface, leading to enhancement in both the activity and stability. Based on the alloys, multimetals offer a good opportunity to optimize their catalytic properties via varying their atomic ordering. , Apart from the alloy composition, morphology engineering of the Pt-based electrocatalysts serves as another powerful method to booster their catalytic performances. Among various nanocrystals available, the metal nanostructures with a porous architecture have received great attention in electrocatalysis due to their large surface area and thus abundant active sites during catalytic reactions. Moreover, the Ostwald ripening effect can be suppressed owing to the interconnected structures existing in the porous nanostructures, leading to a high electrocatalytic performance .…”
Section: Introductionmentioning
confidence: 99%